2022
DOI: 10.3390/ijms23179540
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Glucose Metabolism in Alzheimer’s Disease Onset and Potential Pharmacological Interventions

Abstract: Alzheimer’s disease (AD) is the most common age-related dementia. The alteration in metabolic characteristics determines the prognosis. Patients at risk show reduced glucose uptake in the brain. Additionally, type 2 diabetes mellitus increases the risk of AD with increasing age. Therefore, changes in glucose uptake in the cerebral cortex may predict the histopathological diagnosis of AD. The shifts in glucose uptake and metabolism, insulin resistance, oxidative stress, and abnormal autophagy advance the pathog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 138 publications
0
24
0
Order By: Relevance
“…A number of postmortem studies have indicated that resistance to insulin and IGF-1, with the aberrant activation of their signaling pathway components, as well as reduced insulin/IGF-1 levels as neurotrophic factors, can be detected in the brains of AD patients [ 43 , 127 , 128 , 129 , 130 ], and these abnormalities are more severe in areas involved in cognitive performance, particularly in the hippocampus [ 131 ]. In fact, the early stages of AD, potentially decades before the development of symptoms, are characterized by deficits in cerebral carbohydrate metabolism that worsen with disease progression [ 40 , 132 , 133 ]. Likewise, insulin-resistant elderly people [ 26 , 134 ], T2D patients with mild cognitive impairment [ 135 , 136 ], and even prediabetic patients with normal cognitive function [ 49 , 134 ] show brain hypometabolism quantified by a decreased uptake of [ 18 F]-FDG (18-fluorodeoxyglucose) detected by PET (positron emission tomography) imaging.…”
Section: Molecular Mechanisms Linking T2d To Admentioning
confidence: 99%
See 1 more Smart Citation
“…A number of postmortem studies have indicated that resistance to insulin and IGF-1, with the aberrant activation of their signaling pathway components, as well as reduced insulin/IGF-1 levels as neurotrophic factors, can be detected in the brains of AD patients [ 43 , 127 , 128 , 129 , 130 ], and these abnormalities are more severe in areas involved in cognitive performance, particularly in the hippocampus [ 131 ]. In fact, the early stages of AD, potentially decades before the development of symptoms, are characterized by deficits in cerebral carbohydrate metabolism that worsen with disease progression [ 40 , 132 , 133 ]. Likewise, insulin-resistant elderly people [ 26 , 134 ], T2D patients with mild cognitive impairment [ 135 , 136 ], and even prediabetic patients with normal cognitive function [ 49 , 134 ] show brain hypometabolism quantified by a decreased uptake of [ 18 F]-FDG (18-fluorodeoxyglucose) detected by PET (positron emission tomography) imaging.…”
Section: Molecular Mechanisms Linking T2d To Admentioning
confidence: 99%
“…Likewise, insulin-resistant elderly people [ 26 , 134 ], T2D patients with mild cognitive impairment [ 135 , 136 ], and even prediabetic patients with normal cognitive function [ 49 , 134 ] show brain hypometabolism quantified by a decreased uptake of [ 18 F]-FDG (18-fluorodeoxyglucose) detected by PET (positron emission tomography) imaging. Interestingly, the central impairment of glucose metabolism has been associated with insulin and IGF-1 resistance [ 40 , 132 , 133 , 137 ] and is mostly apparent in the frontal, parietotemporal, and cingulate cortices [ 134 ], indicating that insulin resistance affects the same regions as those affected by AD [ 54 ], and suggesting a link between central insulin resistance and this neurodegenerative disease.…”
Section: Molecular Mechanisms Linking T2d To Admentioning
confidence: 99%
“…Alzheimer's disease (AD) is clinically manifested as cognitive decline and memory impairment (Reitz and Mayeux, 2014;Liu et al, 2019). It is one of the leading causes of global mortality and the most common type of dementia worldwide (Chornenkyy et al, 2019;Kumar et al, 2022b). And the prevalence of AD has been increasing steadily over the past decades (Nichols et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The major pathological characteristics of AD are beta-amyloid (Aβ) deposits and intracellular neurofibrillary tangles (NFTs) formed by hyperphosphorylated tau protein (Grundke-Iqbal et al, 1986;Selkoe and Schenk, 2003). However, a full understanding of the mechanism is still lacking (Kumar et al, 2022a;Kumar et al, 2022b). Currently, there are still no specific drugs, despite the increasing incidence of AD and the social problems it poses (Moran et al, 2019;Srivastava et al, 2021;Michailidis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation